Optimization of variables for maximizing efficacy and efficiency in aerial spray application to cotton using unmanned aerial systems - Liao, Juan; Zang, Ying; Luo, Xiwen; Zhou, Zhiyan; Lan, Yubin; Zang, Yu; Gu, Xiuyan; Xu, Weiming; Hewitt, Andrew John (International Journal of Agricultural and Biological Engineering, 2019)
Aerial spraying can support efficient defoliation without crop contact. With the recent introduction to unmanned aerial system (UAS) for aerial spraying in China, there is a need to determine the optimum application variables to achieve high efficacy and efficiency with low costs. The present research involved field studies across two annual cotton production seasons in North Xinjiang, China. Four factors, including volume rate (A), tank mix including spray adjuvants (B), flight altitude (C), flight speed (D) and three levels of L9 (34) orthogonal arrays were carried out to optimize the application parameters for three types of UASs. These included different numbers of rotors as follows: four-rotors, six-rotors and eight-rotors. Spray coverage, distribution uniformity (coefficient of variation (CV) of droplet coverage), rates of cotton defoliation and boll opening, application efficiency and cost were measured and assessed. Results showed that: (1) the rates of defoliation and boll opening by aerial cotton defoliant application could meet the requirement of cotton mechanized harvesting; (2) the optimal scenario for the three UASs was A3B2C1D3, Volume rate (A3): 48 L/hm2; Tank mix and concentration (B2): (Tuotulong 225 + Sujie 750 + Ethephon 2250) mL/hm2, Flight altitude (C1): 1.5 m, and Flight speeds (D3) for unmanned helicopters with four-rotors, six-rotors and eight-rotors were 3.12 m/s, 2.51 m/s and 3.76 m/s, respectively. These results can provide guidance for cotton defoliant aerial spraying in China using UAS.Keywords: unmanned aerial system (UAS), unmanned aerial vehicle (UAV), unmanned electric helicopter (UEH), cotton defoliant, aerial spraying, parameter optimizationDOI: 10.25165/j.ijabe.20191202.4288Citation: Liao J, Zang Y, Luo X W, Zhou Z Y, Lan Y B, Zang Y, et al. Optimization of variables for maximizing efficacy and efficiency in aerial spray application to cotton using unmanned aerial systems. Int J Agric & Biol Eng, 2019; 12(2): 10–17.